2012
DOI: 10.1093/infdis/jis730
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Effector Function of CD8+ T Cells From Healthy Controls and HIV-Infected Patients Occurs Through Thrombin Activation of Protease-Activated Receptor 1

Abstract: Disruption of vascular integrity by trauma and other tissue insults leads to inflammation and activation of the coagulation cascade. The serine protease thrombin links these 2 processes. The proinflammatory function of thrombin is mediated by activation of protease-activated receptor 1 (PAR-1). We found that peripheral blood effector memory CD4(+) and CD8(+) T lymphocytes expressed PAR-1 and that expression was increased in CD8(+) T cells from human immunodeficiency virus (HIV)-infected patients. Thrombin enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 46 publications
5
41
0
Order By: Relevance
“…Less is known about the effects of PAR-1 activation on adaptive immune cells. We found that treatment with thrombin induces dose-dependent PAR-1 internalization in CD8 + T cells and confirmed an earlier report that thrombin augments IFN-γ production in purified CD8 + T cells in vitro [20]. This effect was also seen with the PAR-1 agonist TFLLR and could be blocked in both cases with the PAR-1 antagonist vorapaxar.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Less is known about the effects of PAR-1 activation on adaptive immune cells. We found that treatment with thrombin induces dose-dependent PAR-1 internalization in CD8 + T cells and confirmed an earlier report that thrombin augments IFN-γ production in purified CD8 + T cells in vitro [20]. This effect was also seen with the PAR-1 agonist TFLLR and could be blocked in both cases with the PAR-1 antagonist vorapaxar.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the findings of Catalfamo et al [20], there was a small but significant increase in the percentage of CCR7 neg CD8 + T cells that exhibited IFN-γ production in the presence of thrombin ( Figure 5A), and the enhancement could be blocked with vorapaxar. Surprisingly, when we repeated the stimulation experiments with unseparated PBMC preparations, we observed an neg CD8 + T cells expressing IFN-γ in PBMC cultures after stimulation with anti-CD3/anti-CD28 for 6 hours in the absence (0 U/mL) or presence (0.5 U/mL) of thrombin (n = 9; right).…”
Section: T Cells With Thrombin Induced Par-1 Internalization On Cx3cr1supporting
confidence: 91%
See 3 more Smart Citations